Desempenho de estações de tratamento de esgoto e impactos de seus efluentes em corpos de água receptores em Minas Gerais - Luís Fernando de Morais Silva (2020)
Domestic sewage represents the main pressure on Brazil's water resources due to the absence or inefficiency of wastewater treatment. The analysis of data from the monitoring of wastewater treatment plants (WWTPs) allows diagnosis and definition of strategies that aim the rational use of water resources and propitiate the multiple use of water, with a consequent increase in water security. Therefore, the objective of this research is to analyze the performance of WWTPs and the impact of the discharge of its effluents on the water quality of the receiving bodies located in Minas Gerais. For this, secondary monitoring data, comprised between 2006 and 2019, of 49 WWTPs in Minas Gerais and their respective receiving bodies were analyzed statistically. The analysis included: verification of compliance with the normative standards for the discharge of effluents and water quality; comparison of the influents and effluents of the WWTPs by treatment modality; comparison of the influents and effluents of the WWTPs by station size and comparison of the water quality of the receiving bodies upstream and downstream of the discharges. The results showed an increase in violations of the legislation after the discharge of effluents from the WWTPs, especially for the parameters total ammoniacal nitrogen and surfactants, which do not have a discharge pattern applicable to public sewage systems. High percentages of violations of water quality standards were found even upstream of the WWTPs, indicating the need for wide-ranging actions to recover hydrographic basins in order to ensure greater water security. The comparison of stations by size identified that, in general, treatment in larger WWTPs resulted in lower concentrations of pollutants in the treated sewage. The comparison of treatment modalities identified worse performances for anaerobic modalities, especially those using UASB reactors. Despite being more efficient and presenting lower percentages of violation of the normative standards, the WWTPs that use aerobic technologies also caused water pollution, highlighting the need to improve treatments to guarantee water security.